Pengaruh DER, CR dan PBV Terhadap Harga Saham Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Tahun 2016 – 2020 - Ulfi Zuslaini; Syahyunan Syahyunan; Zuwina Miraza (Jurnal Ekonomi Bisnis Digital, 2022)
This study aims to determine the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Price to Book Value (PBV) on stock prices with dividend policy as an intervening variable listed on the Indonesia Stock Exchange (IDX). This research is a causal associative study and the type of data used is quantitative data. The population of this study is manufacturing companies in the consumer goods industry sector for the 2016-2020 period, which amounted to 68 companies. The sample in this study totaled 21 companies. The data used is secondary data in the form of annual reports and company financial statements that have been audited on the Indonesia Stock Exchange during the 2016-2020 period. Data that is ready to be processed will be carried out statistical testing using the SmartPLS program. The results of this study show that the Debt to Equity ratio (DER) has a positive and insignificant effect on dividend yield, Current Ratio (CR) has a positive and insignificant effect on dividend yield, Price to Book Value (PBV) has a positive and insignificant effect on dividend yield, Debt to Equity ratio (DER) has a negative and significant effect on stock price, Debt to Equity ratio (DER) has a negative and significant effect on stock prices, Price to Book Value (PBV) has a positive and insignificant effect on stock prices, dividend yield has a negative and insignificant effect on stock prices, and dividend yield are unable to mediate the effect of Debt to Equity ratio (DER), Current Ratio (CR), and Price to Book Value (PBV) on stock prices.